Socioeconomic Consequences of Corruption and Financial Crimes - Kulmie, Dayah Abdi; Hilif, Mohamud Dahir; Hussein, Mukhtar Sheikh (International Journal of Economics and Financial Issues, 2023)
Corruption and financial crimes are major obstacles to the socioeconomic development of many countries in the world. This study employed descriptive research design to assess the socioeconomic consequences of these crimes. The data were collected through questionnaire from 200 respondents. The study results indicate that financial crimes and corruption both have significant socioeconomic consequences by destroying public confidences, weakening public service delivery such as education, health service, it also demolishes private sector particularly small business growth which ultimately affect employment level, GPD and, life expectancy, defeat culture, values, ethics of the society and finally eliminates trust, partnership and collaboration among business organization, public institutions, and society. Moreover, the socioeconomic consequences of these crimes include inequality and poverty in the country. The study recommends strengthening the capacity of public institutions, good governance, strengthening internal control systems, establishing effective monitoring frameworks, promoting accountability and transparency of the public sector, establishing legal frameworks and anti-corruption strategies, and supervision mechanisms in public institutions.